2008
DOI: 10.1089/thy.2007.0412
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinase 2 (MMP-2) and Tissue Inhibitor of Metalloproteinase 2 (TIMP-2) in Medullary Thyroid Carcinoma: Prognostic Implications

Abstract: Immunohistochemical expression of MMP-2 in thyroid surgical specimens from patients with MTC is a novel indicator of the prognosis of this cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…In previous research,39,40 we observed a correlation between prognosis and the immunohistochemical expressions of metalloproteinases—enzymes related to the extracellular matrix and basement membrane degradation—in MTC surgical specimens. However, statistical parameters, such as sensitivity and specificity, showed that the presence of cervical lymph node metastases and TNM stage were the major variables.…”
Section: Discussionmentioning
confidence: 66%
“…In previous research,39,40 we observed a correlation between prognosis and the immunohistochemical expressions of metalloproteinases—enzymes related to the extracellular matrix and basement membrane degradation—in MTC surgical specimens. However, statistical parameters, such as sensitivity and specificity, showed that the presence of cervical lymph node metastases and TNM stage were the major variables.…”
Section: Discussionmentioning
confidence: 66%
“…Production of proMMP2 and MT1-MMP has previously been shown in human PTC and MT1-MMP expression levels correlated with the proMMP2 activation ratio, thyroid cancer cell invasion, and PTC lymph node metastasis (31,35). Similarly, a positive correlation was reported for the presence of immunoreactive MMP2, but not TIMP2, and bad prognosis of patients with medullary thyroid cancer, a tumor derived from C-cells in the thyroid gland (51). Expression of gelatinase A (MMP2), gelatinase B (MMP9), and MT-MMP1 has also been reported in breast, colon, lung, skin, ovary, and prostate cancer and is associated with enhanced invasion and decreased overall survival (52)(53)(54).…”
Section: Discussionmentioning
confidence: 73%
“…Two transcript variants encoding different isoforms have been found for this gene. A recent study assessing a panel of MTC cancer specimens found that expression of MMP2 could be used as a prognostic tool (Cavalheiro et al, 2008). …”
Section: Genes Involved and Proteinsmentioning
confidence: 99%